School leadership and improvement of educational process Theoretical perspective on importance and roles - SAKHRI, Mohamed (Social Empowerment Journal, 2021)
School leadership is essential in schools because of its strategic role in education. It is peracticed through polycies based on given objectives of society. Thus, school leadership aims at acheiving some general and specific goals that can appear in scholars’ activities. It provides also a suitable environment for learning process. Therfore, school leadership shoul be an organized process which aim is to have an impact on scholars’ behavior for achieving previousely planned objectives. The main feature of the school leadership lies behind stimulating the educational actors through educational, artistic, and technical inputs which are then purued to get as outcomes educational, social, and economic impacts. This paper aims at understanding the importance and roles of school leadership for improving both the teaching and learning process.